Architectural Ecotone: The Edge Effect - Metzger, Holly; Nuqul, Tara (SURFACE at Syracuse University, 2019)
This thesis aims to study the relationship between architecture and its environment. Specifically, this thesis will explore symbiotic relationships between architecture and surrounding ecosystems in many different terrains. Iceland presents a particular important case for this idea because it is a hotbed of geological activity. The country itself is a patchwork of desert, glaciers, geysers, lava fields and active volcano, which has led to Iceland developing intelligent systems of vernacular architecture throughout history to mediate this environment. This thesis studies systems of domestic vernacular architecture by examining the qualities and characteristics of craft, materiality, structure, and a symbiotic relationship to its environment. More specifically, the thesis examines Icelandic turf housing, because it is adaptive and mediative to its natural environment and utilizes the landscape to its design benefits. Turf Housing was built by Icelandic settlers, using the nutrient-poor sod from the grassland as a seven-foot layer of insulation covering birch frames forested in Iceland, and provides shelter and warmth for people and animals. The vernacular is also of interest because of its ability to respond and adapt to the scarcity, inaccessibility, and unpredictability of the Icelandic environment. Iceland is a hotbed of geological activity; it is a patchwork of desert, glaciers, geysers, lava fields and active volcanoes. There are no boundaries between the many ecosystems, rather overlaps or moments of displacement referred to as ecotones, defined as " a region of transition between two biological communities." We can apply the concept of ecotones to architecture to create a transitional area between two different environments: the built and the natural. This thesis brings traditional vernacular methods of mediation into contemporary needs of ecosystems, by using the concept of ecotones to create a symbiotic relationship between object and terrain. The specific project through these ideas will be tested is a ...